Design and Implementation of a QR Code-Based Attendance Application at SMA Negeri 1 Cangkringan - Muhammad Hilmiawan Sulthoni; Vikky Aprelia Windarni; Surya Tri Atmaja; Dewi Anisa Istiqomah; Fiyas Mahananing Puri (Politeknik Piksi Ganesha Indonesia, 2025)
The manual attendance system at SMA Negeri 1 Cangkringan still faces various obstacles, such as the time-consuming recording process, the risk of data loss, and the possibility of manipulating student attendance. Overcome these problems, a web-based student attendance application was developed using the Waterfall method. The method used in completing this system is the waterfall method, which consists of needs analysis, system planning, development, and testing. The system is designed using web technology, which allows better accessibility for teachers and administrative staff in recording attendance in real-time. The result of the user-friendly application design, allows teachers to record student attendance quickly and accurately. The system is also a report feature that can be accessed easily, making it easier to make decisions regarding student attendance. It is expected that the administration process at SMA N 1 Cangkringan can be more efficient, transparent, and reliable.